Reflective journals for the enhancement of postgraduate students learning: an Australian case study - Issa, Tomayess; Issa, Theodora; Isaias, Pedro (Common Ground Publishing LLC, 2012)
The aim of this paper is to examine the value of learning through ‘Reflective Journal Assessment’ in IS6 and ITS6 Postgraduate units at an Australian University. This assessment goes beyond traditional teaching delving into the higher faculties of students’ mental abilities. This is achieved by providing them with the opportunity to critically analyze, and creatively form opinions on issues related to the topics being taught either through the analysis of peer-reviewed journal articles, or chapters from text books. This assessment is coupled with the students’ reflection on their understanding, abilities, and how such an exercise developed their thoughts and comprehension and cognitive abilities. Furthermore, this assessment is designed to allow students’ self-awareness and self-knowledge in respect to the contents, thus improving their writing, research, and analytical skills. This paper provides empirical evidence based on quantitative and qualitative data derived from two sources. The first is the anonymous informal feedback collected during the semester, while the second (the formal) is the other anonymous online system for gathering and reporting students’ perceptions of their learning experiences at the university ‘eValuate’ of 53 students’ evaluations and perspectives toward the IS6 and ITS6 units. The students’ comments reflect their satisfaction of the opportunity to be involved in such thought-provoking exercise appraising the reflective learning exercise at postgraduate level.